Doc Martin. Series 4 [videorecording (DVD)] - Bolt, Ben, 1952-; Clunes, Martin, 1961-; Catz, Caroline; Williams, Lia; Cole, Stephanie, 1941-; McNeice, Ian (Acorn Media, 2010)
Doc Martin continues his misanthropic adventures in the idyllic seaside village of Portwenn. The fourth season of the hit dramedy sees two unexpected arrivals that complicate the good doctor's already messy life. Contains eight episodes.